Transformational leadership : challenges for leaders at the National Institute for Higher Education in the Northern Cape (South Africa) - Laubscher, Teresa (Stellenbosch : Stellenbosch University, 2008)
Thesis (MPhil (Curriculum Studies))--Stellenbosch University, 2008.